Ruptured Uterus in Primi Para - Tanweer Sana; Shama Chaudhry; Rubina Hussain (ziauddin University, 2024)
ABSTRACT Rupture of a gravid uterus is a surgical emergency. Spontaneous rupture of the uterus in a primipara is very rare. Furthermore, uterine rupture prior to the onset of active labor is extremely uncommon in a primipara, with very few reported cases. We present a case of antepartum uterine rupture in a 23-year-old gravida 2 para 0+1 with 26 weeks pregnancy in whom the clinical features resembled those of abruptio placentae. She had past history of one uterine curettage and now presented with 26 weeks pregnancy& abdominal pain of sudden onset. After ultrasound scan, uterine rupture was diagnosed and an emergency laparotomy done. The entire amniotic sac was found in the peritoneal cavity with a rupture of the uterine fundus. KEY WORDS: Primipara, Uterine Curettage, Antepartum, Uterine rupture.